Cyberbullying bystanders and moral engagement: a psychosocial analysis for pastoral care. (3rd April 2018) - Kyriacou, Chris; Zuin, Antônio
Abstract: One of the new challenges facing pastoral care in schools is dealing with the rapid growth of cyberbullying by school-aged children. Within digital cyberspace, cyberbullies are finding more opportunities to express their aggression towards others as social networks become technologically more sophisticated. An important feature of cyberbullying is the extent to which hostile messages can go viral, in the sense that they are seen and then forwarded to others many times over. This paper considers psychosocial aspects of why cyberbullying messages can go viral, and what can be done to reduce this phenomenon. This paper focuses on the role of the hostile cyberbullying bystander (viz. the person who receives and then forwards to others a cyberbullying message). Finally, we develop intervention strategies based on pastoral care, which may be effective in inhibiting hostile cyberbullying bystander behaviour.